Representasi Budaya Lokal dalam Media Sosial : Studi Kasus Tradisi Omed-omedan di Akun Tiktok @melalibali - Ni Made Sumiartini Putri Erdani; Rieka Yulita Widaswara; I Nengah Putra Kariana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of digital technology has significantly transformed the way society accesses, shares, and disseminates information across various online platforms. This transformation has not only influenced the fields of communication and entertainment but has also played an important role in the preservation, promotion, and revitalization of local culture in the modern era. This study aims to examine how the Omed-Omedan tradition, one of Bali’s unique and meaningful cultural practices, is represented through the TikTok account @melali.bali, as well as how public perception is shaped and influenced by this digital representation. Using a descriptive qualitative content analysis method, the study explores visual forms, narratives, and user interactions with content featuring the Omed-Omedan tradition. The findings reveal that the @melali.bali account consistently presents content with high aesthetic value, educational narratives, and strong social and spiritual messages. TikTok has proven to hold great potential as an inclusive, participatory, and educational medium for cultural representation. The positive audience response demonstrates that social media can serve as an effective tool in maintaining the relevance of local culture while broadening its understanding in the global context.